Remote Control of Electron Transfer Reaction by Microwave Irradiation: Kinetic Demonstration of Reduction of Bipyridine Derivatives on Surface of Nickel Particle - Kishimoto, Fuminao; Matsuhisa, Masayuki; Imai, Takashi; Mochizuki, Dai; Tsubaki, Shuntaro; Maitani, Masato M; Suzuki, Eiichi; Wada, Yuji (The journal of physical chemistry letters, 2019)
Microwave irradiation has great potential to control chemical reactions remotely, particularly reactions that involve electron transfer. In this study, we found that the reduction reaction of bipyridine derivatives on metal nickel particles was accelerated or decelerated by 2.45 GHz microwaves without an alteration of the reaction temperature. The order of the extent of the microwave acceleration of the electron transfer reaction coincided with the negativity of the redox potential of the bipyridine derivatives, i.e., the electron transfer with smaller ΔG was significantly enhanced by microwave irradiation. By applying Marcus’ electron transfer theory, we propose two mechanisms of the microwave effect on electron transfer reactions, i.e., vibration of the electrons in Ni particles to make the electron transfer easier and rotation of the water molecules to prevent the reorganization of the hydrated systems after the electron transfer reaction.